WAY and TREE as Manifestants of Ukrainian Mythological and Poetical Space - Філон, Микола Іванович; Хомік, Олена Євгеніївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article deals with the peculiarities of folk world picture organization in connection with the concept TREE as an attribute of the way. Manifestations of axiological semantics of mythological and poetical link WAY – TREE in various genre of folk philology are found out. The link of tree and way images in their projection at the specificity of the world modeling in the texts of different genres is described. Mythological and poetical determinants of the usage of the constituents of the concept TREE depending on genre specialization of the text and its world-view filling are defined.